The Effect of Information Deception in Price Comparison Site on the Consumer Reactions: An Empirical Verification. (28th September 2015) - Lee, Un-Kon
Challenges in the ubiquitous networks deployment are to guarantee the information transparency in the distributed systems. In particular in online market, studies warned that information deception by online sellers and by price comparison site could be fatal in the success of e-marketplace. However, handful of studies had conducted this issue and the findings are still mixed and ambiguous. I challenged to empirically validate the impact of information deception by the price comparison site on the consumer behavioural intentions. I developed the research model based on the literature of information transparency, information deception, institution-based trust, psychological contract violation, and consumer reactions. I conducted the quasi-experiment in two types of price comparison sites. The results of this study had successfully captured the existence and impact of information deception, could contribute to providing more rigorous evidence for the theory, expand the consumer protection research area in IS filed, and suggest the need for the neutral price comparison site for the success of e-marketplace to the regulatory party.